2015
DOI: 10.1021/acs.iecr.5b00555
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Radial Adsorber with Parallel Layered Beds for Prepurification of Large-Scale Air Separation Units

Abstract: The scale of cryogenic air separation units (ASUs) has increased continuously in recent years.In order to better meet the requirements of large-scale ASUs in terms of achieving both good prepurification performance and energy-saving effects, a novel radial adsorber with parallel layered adsorbent beds is proposed in the present paper. The main purpose of the novel adsorber is to reduce the pressure drop and increase the adsorption performance with a relatively compact structure, which may gain long-term energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The calculation results show that this design can effectively solve the problem of uneven flow field. Tian et al [16] proposed a novel radial adsorber by parallel layered beds. By the numerical simulation analysis, the results showed that this design could better meet the requirements of large-scale air separation in terms of achieving good pre-purification performance under the premise of low energy consumption.…”
Section: Gravity Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation results show that this design can effectively solve the problem of uneven flow field. Tian et al [16] proposed a novel radial adsorber by parallel layered beds. By the numerical simulation analysis, the results showed that this design could better meet the requirements of large-scale air separation in terms of achieving good pre-purification performance under the premise of low energy consumption.…”
Section: Gravity Directionmentioning
confidence: 99%
“…The relevant sizes are shown in Tables 1-2. A two-dimensional (2D) axisymmetric finite element model has proven to be applicable by Tang [14], Tian [16] and Li [17]. Comparing with 3D model, 2D axisymmetric model can reduce computational complexity and shorten the computing period.…”
Section: Cfd Simulation Of Adsorption and Desorption Process 21 Geommentioning
confidence: 99%
“…In addition to that, Sakwa-Novak et al evaluated a At present, RFRs have not been investigated for the application of CO 2 direct air capture. In the past two decades, RFRs were studied in some research papers and patents for, e.g., (1) configurations for a uniform flow distribution [31][32][33], (2) the application of catalytic reactions to produce naphtha [34,35], xylenes [36], methanol [37], or hydrogen [38], and (3) the application of air purification (prior to the cryogenic air separation unit) [39]. No other studies evaluated RFRs for DAC using a supported amine sorbent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, radial flow adsorber (RFA) has the characteristics of large cross-sectional area, large flow capacity, gas distribution uniformity, small flow resistance and large feed flowrate [4,5]. It has been widely used in chemical industry, petrochemical and gas production industry [6,7]. However, due to the extremely complex variable mass flow caused by the internal structure of RFA, one of the most important issues to be solved for heat and mass transfer in two-phase flow in RFA is model verification [8].…”
Section: Introductionmentioning
confidence: 99%